Poststructural Analysis of the Role of Reader - Rizvanović, Nenad E. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper discusses how post-structuralist theory deals with the concept of the reader’s aesthetic role in the process of reading literature. The relationship between authors, texts, and readers is regarded as the key-point of theoretical analysis among many relevant scholars and literary theorists (Umberto Eco, Wolfgang Iser, Jonathan Culler, Peter Rabinowitz, Stanley Fish), who have all contributed to our understanding of this topic by introducing fundamental concepts such as “the implied reader”, “the ideal reader”, “the informed reader” or “the authorial reader”. While formalism and structuralism have considered the reader to be an abstract, ahistorical figure, without any relevant share in the establishment of meaning in any given literary work, post-structuralism discusses the role of the reader in the act of reading not only as the crucial factor in the process of aesthetic experience but also as the essential condition for generating meaning as such.